Operacionalização do eixo ―práticas de análise linguística‖ em livros didáticos de língua portuguesa. - Araújo, Nathalia (Universidade Federal do Tocantins, 2022)
This work, in the light of the peuchetiana discourse theory, discusses how the axis "Linguistic analysis of Practice" is mobilized in two textbooks Portuguese. This axis consists of the Parâmetros Curriculares Nacionais (PCN), the Portuguese language, the primary education, basic education, to characterize and structure the Portuguese language as a teaching and learning object. These parameters began to replace other terms, including methodological, the language teaching, language, normative grammar and literature. It is the anchor in the text received a prominent place, the point of it being conceived as a theoretical and methodological approach. So, linguistic, grammatical and literary issues should take them as a basis. To that extent, this work is to analyze and discuss how that axis gets a operationalization in some textbooks Portuguese, considering the reframing in terms of official guidelines of teaching, that teaching went. Therefore, we consider the constant official guidelines of the PCN and the Programa Nacional do Livro Didático (PNLD) shows is essential to apprehend the conditions of production of textbooks in the Brazilian educational scenario, since these guidelines contain certain discourses, the as they are read and interpreted. The analysis of two books show the different way to mobilize the relevant axle; in a book, there is a way to approach this axis more arrested in and the text, given the rules of the didactic sequence, however, in another book, the approach still shows so more ignorant, superficial.